Pengembangan Media Pembelajaran Mobile Learning Berbasis Android Untuk Meningkatkan Hasil Belajar Siswa Kelas X SMA - Ardhian Singgih Pamungkas; Indri Astuti; Eny Enawaty (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2023)
The Covid-19 pandemic has changed the order of human life from various aspects of life. One of them is the educational aspect. The educator aspect had experienced quite serious problems, namely the implementation of the learning process that was not running optimally. Therefore, a solution is needed that is suitable for each of these learning problems. This study aims to develop Android-based mobile learning media to increase students' interest and learning outcomes. The subjects of this study were students of class X High School (SMA). This research method uses Research and Development with the 4D research model Define, Design, Develop, and Dissiminate). The results of this study indicate the validity level of learning material experts is 88% and is included in the very good category, the validity level by learning media experts is 85% and is included in the very good category, and the validity level by multimedia experts is 87% and is included in the very good category. Based on the results of this study, it was stated that Android-based mobile learning media was effectively applied in the learning process in class X High School (SMA).